2011
DOI: 10.3892/ijmm.2011.801
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus-specific cellular and humoral immune responses following immunization with a multi-epitope fusion protein

Abstract: Abstract. Hepatitis C virus (HCV) is an important causative agent of acute and chronic hepatitis worldwide. We prepared a fusion protein in the vector of pET-11d that included three conserved broadly neutralizing B-cell epitopes and a series of T-cell epitopes located in the HCV NS3 region. In vivo administration of this fusion construct resulted in specific CD8 + cytotoxic lymphocytes in both PBMCs and splenocytes that could recognize specific antigen sites that could be detected by FACS. An HCVcc system was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Alternatively, differences in virus-host cell interactions produced by the E1B55K deletion might have stimulated Ad- and HIV-specific innate and adaptive immune responses that compensated for the increased levels of immunogen promoted by the wild-type virus. Indeed, differences in peptide and protein immunogen concentrations as little as 3- to 5-fold have led to detectable changes in immune responses [ 26 , 27 ]. For that reason, we expected the E1B55K wild-type vector to produce measurably higher immune responses in the immunized mice.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, differences in virus-host cell interactions produced by the E1B55K deletion might have stimulated Ad- and HIV-specific innate and adaptive immune responses that compensated for the increased levels of immunogen promoted by the wild-type virus. Indeed, differences in peptide and protein immunogen concentrations as little as 3- to 5-fold have led to detectable changes in immune responses [ 26 , 27 ]. For that reason, we expected the E1B55K wild-type vector to produce measurably higher immune responses in the immunized mice.…”
Section: Discussionmentioning
confidence: 99%
“…Additional strategies include molecules that induce innate immune responses, with secondary effects on adaptive responses (such as TLR‐9 ligands) that are either encoded within a vaccine construct or used as a vaccine adjuvant. Qiu et al (12) prepared a fusion protein in the vector of pET‐11d that included 3 conserved broadly neutralising B‐cell epitopes and a series of T‐cell epitopes located in the HCV NS3 region. In vivo, administration of this fusion construct resulted in specific CD8+ cytotoxic lymphocytes that recognised specific antigen sites that were detected by fluorescence activated cell sorter.…”
Section: Plans To Achieve the Goalsmentioning
confidence: 99%
“…Potent new direct acting antivirals (DAAs) have dramatically improved the success rates in disruption of the viral replication; however, high costs, side effects, and treatment failures still remain the main issues, underscoring the importance of developing therapeutic/prophylactic vaccines [25]. Several studies have shown that NS3 protein is a promising antigen for the purpose of anti-HCV vaccine development [26,27]. However, subunit vaccines induce a lower immune response compared to whole cell vaccines, requiring improved vaccine carriers/adjuvants [28].…”
Section: Discussionmentioning
confidence: 99%